PENGARUH POC HPA INTERNATIONAL DAN NPK ORGANIK TERHADAP PERTUMBUHAN SERTA PRODUKSI JAGUNG PELANGI (Zea mays L.) - Sarbani; Fathurrahman (DINAMIKA PERTANIAN, 2025)
Research entitled "The Effect of HPAI POC and Organic NPK on the Growth and Production of Rainbow Corn (Zea mays L.)" was conducted at the Experimental Farm of the Faculty of Agriculture, Universitas Islam Riau, Jalan Kaharuddin Nasution KM 11, No. 113, Air Dingin Village, Pekanbaru, from August to November 2023. The purpose of the study was to determine the effect of the interaction between HPAI POC and Organic NPK fertilizer on the growth and production of rainbow corn plants. This study employed a Completely Randomized Design (CRD) factorial consisting of two factors: the first factor involved the application of HPAI POC doses with five treatment levels, namely without HPAI POC, 2, 8, 14, and 20 cc/l. The second factor in the application of Organic NPK fertilizer included the treatment levels: without Organic NPK and 50, 100, and 150 g/plot. The parameters observed were plant height, number of leaves, harvest age, weight of cobs without husks, weight of cobs with husks, and weight of 100 seeds. The observation data were analyzed statistically and followed by further BNJ tests at the 5% significance level. The results showed that the effects on growth and production of rainbow corn plants from the application of HPAI POC and Organic NPK fertilizers were significant for plant height, number of leaves, weight of cobs without husks, weight of cobs with husks, and weight of 100 seeds. The best combination of treatments was HPAI POC at 20 cc/l and Organic NPK at 150 g/plot. The main effect of HPAI POC was significant for all observation parameters. The best treatment was at a concentration of 20 cc/l. The main effect of Organic NPK fertilizer was significant for all observation parameters. The best treatment was at a concentration of 150 g/plot.